Assessment of Prosthodontic Status and Treatment Needs of Patients Visiting Dental Institutions of Punjab - Akshey K. Sharma; Kavipal Singh (Wolters Kluwer Medknow Publications, 2024)
Background: This study was conducted to assess the prosthodontic status and treatment needs of patients visiting dental institutions of a known population. Material and Methods: This study comprised a total of 100 participants. The research excluded patients who did not have any prosthodontic appliances or who had dental crowns (no missing teeth). The subjects involved in the study had dental bridges, dentures, removable partial dentures, or a combination of the two. Subjects in the research were asked to tell their education, oral hygiene routines, and dentist visit behaviors. The data collected was utilized to determine the association between the variables and prosthodontics status. A thorough clinical examination of these subjects was done. The data had been analyzed using the statistical program SPSS 13. The analyses were carried out using Chi-square tests and the appropriate C-coefficient. Results: In this study, there were 50 males and 50 females. Out of 100 subjects, 45 subjects were found to be completely edentulous without any prosthodontic appliance. Complete dentures were noticed in 11 subjects, removable dentures in 29 subjects, and fixed appliances in 15 subjects. Conclusion: This survey presented that most of the subjects were completely edentulous without any prosthetic appliance. Examination of such subjects must be done on a regular basis and an appropriate treatment plan must be constructed for the well-being of these patients.